2021
DOI: 10.1038/s41598-021-83682-3
|View full text |Cite
|
Sign up to set email alerts
|

Volume-based algorithm of lung dose optimization in novel dynamic arc radiotherapy for esophageal cancer

Abstract: This study aims to develop a volume-based algorithm (VBA) that can rapidly optimize rotating gantry arc angles and predict the lung V5 preceding the treatment planning. This phantom study was performed in the dynamic arc therapy planning systems for an esophageal cancer model. The angle of rotation of the gantry around the isocenter as defined as arc angle (θA), ranging from 360° to 80° with an interval of 20°, resulting in 15 different θA of treatment plans. The corresponding predicted lung V5 was calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Low-dose radiation could be a signi cant predictor of RP (14,15,30). Based on the VBA (17), the present study used the 5 Gy isodose curve to distinguish HD (≧ 5 Gy) and LD (< 5 Gy) regions in the lung volume to assess the relationship between metabolic response and absorbed dose. There were statistically signi cant increases in the SUVmax, SUVmean, and GLG of HD regions between pre-and post-RT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low-dose radiation could be a signi cant predictor of RP (14,15,30). Based on the VBA (17), the present study used the 5 Gy isodose curve to distinguish HD (≧ 5 Gy) and LD (< 5 Gy) regions in the lung volume to assess the relationship between metabolic response and absorbed dose. There were statistically signi cant increases in the SUVmax, SUVmean, and GLG of HD regions between pre-and post-RT.…”
Section: Discussionmentioning
confidence: 99%
“…According to the VBA established by our team (17), we proposed the VBA method to reduce lung V5 in dynamic arc-based RT. Therefore, we integrated the irradiated lung volume in RT planning and volumebased parameters in PET/CT.…”
Section: Computed Tomography Simulation and Radiation Treatment Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the treatment arc angle selection, the personalized OPA angle could be calculated using VBA for each patient according to Eqs. ( 1 )–( 2 ) 15 . The width of the PTV (E) was measured on the axial plane, while the axial length of the PTV (Lt) was measured vertically on the coronal image of the centroid of the PTV.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we proposed the volume-based algorithm (VBA) method to quickly calculate the optimal partial arcs (OPA) angle corresponding to the lung V 5 by defining the length and width of the planning target volume (PTV) 15 . We demonstrated that VBA could improve the efficiency of VMAT planning to reduce the lung V 5 within 5 min in a phantom study.…”
Section: Introductionmentioning
confidence: 99%